(untitled) (British Journal of Global Ecology and Sustainable Development, 2022)
This article talks about the study of the elements of the technology of growing high-quality cotton from the Namangan-77 variety of cotton in the conditions of the grassland saz soils of the Fergana region of our country, and this process is considered.